2020
DOI: 10.3390/ma13051215
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coating to Minimize Corrosion of Glass-Ceramics for Dental Applications

Abstract: The effect of a novel silicon carbide (SiC) coating on the chemical durability of a fluorapatite glass-ceramic veneer was investigated by examining weight loss and ion release levels. The hypothesis that this novel coating will exhibit significant corrosion resistance was tested. Inductively coupled plasma atomic emission spectrometer (ICP) was used for ion concentration determination and scanning electron microscopy (SEM) for surface morphology analyses. Samples were immersed in pH 10 and pH 2 buffer solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…This study confirmed that SiC coating can decrease bacterial adhesion on the surface of ceramic veneers while maintaining biocompatibility with other cells. SiC recently demonstrated optimized color properties and corrosion resistance [21,22]. This coating can be applied to dental materials to improve their clinical performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study confirmed that SiC coating can decrease bacterial adhesion on the surface of ceramic veneers while maintaining biocompatibility with other cells. SiC recently demonstrated optimized color properties and corrosion resistance [21,22]. This coating can be applied to dental materials to improve their clinical performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al [21] reported that SiC-coated dental ceramics demonstrated a significant reduction in corrosion when placed in caustic environments that represent the extreme conditions of the oral cavity. Chen et al [22] demonstrated that the thickness of the SiC coating can also be optimized to match any tooth shade required within the dental field.…”
Section: Introductionmentioning
confidence: 99%
“…Out of many potential materials that could protect titanium from corrosion, silicon carbide (SiC) seems promising due to this material’s high strength, lack of reactivity to the oral environment, and ease of deposition [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Using SiC as a protective coating has proven to be effective for glass-ceramics used for fixed dental prostheses and significantly reduced the effects of corrosion [ 54 , 56 ]. In addition to SiC’s durability, this coating has also shown favorable biocompatibility in various applications [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide is extremely inert material, that is why the development of bio-based SiC ceramic technology is very important today for bio and medical applications [1][2][3][4]. Analysis of the erosive effect of different substance and medications has shown that different pH levels affect the surface of dental ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…CVCs(1)(2)(3) and their dimensionless sensitivity α (curves 1'-3') of SiC films on Si at different bias voltage Vbias: Vbias = 0 (1) and Vbias = -200 V (2); on insert the glass is substrate.…”
mentioning
confidence: 99%